Uranium hydrogeochemical and stream sediment reconnaissance data from the area of the Shishmaref, Kotzebue, Selawik and Shungnak Quadrangles, northern Seward Peninsula and vicinity, Alaska - Warren, R.G.; Hill, D.E.; Sharp, R.R. Jr. (Los Alamos Scientific Laboratory, 1978)
During the summer of 1976, 1336 water and 1251 sediment samples were collected for Los Alamos Scientific Laboratory (LASL) from 1356 streams and small lakes or ponds within Shishmaref, Kotzebue, Selawik, and western portion of Shungnak NTMS quadrangles in western Alaska. Both a water and sediment sample were generally obtained from each location at a nominal location density of 1/23 km/sup 2/. Total uranium was measured in waters by fluorometry and in sediments and a few waters by delayed neutron counting at LASL. Uranium concentrations in waters have a mean of 0.31 ppB and a maximum of 9.23 ppB, and sediments exhibit a mean of 3.44 ppM and a maximum of 37.7 ppM. A large number of high-uranium concentrations occur in both water and sediment samples collected in the Selawik Hills. At least two locations within the Selawik Hills appear favorable for further investigation of possible uranium mineralization. A cluster of high-uranium sediments, seen in the Waring Mountains, are probably derived from a lower Cretaceous conglomerate unit which is assocated with known airborne radiometric anomalies. Apparently less favorable areas for further investigation of possible uranium mineralization are also located in the Waring Mountains and Kiana Hills. Additional samples were collected within the Shungnak quadrange to increase the sampling density used elsewhere in the area to about one location per 11 km/sup 2/ (double-density). Contoured plots of uranium concentrations for both waters and sediments were prepared for all double-density sample locations, and then for the even-numbered and odd-numbered locations separately. These plots indicate that the HSSR sampling density of 1/23 km/sup 2/ used in lowland areas of Alaska provide essentially the same definition of relative areal uranium distributions in waters and sediments as seen when the density is doubled. These plots indicate that regional distribution patterns for uranium are well defined without selective sampling of geologic units.